PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK DAN EXPERIENTIAL MARKETING TERHADAP KEPERCAYAAN KONSUMEN YANG BERDAMPAK PADA MINAT BELI ULANG KONSUMEN TOKO IJEN MART MAESAN - BONDOWOSO - Uswatun Hasanah; Lusiana Tulhusnah; Randika Fandiyanto (Fakultas Ekonomi dan Bisnis, 2025)
Store’s implementation of ideal marketing management principles. This study aims to analyze the influence of service quality, product diversity, and experiential marketing on consumer trust and its impact on repurchase intention at Ijen Mart Store in Maesan - Bondowoso. This inconsistency raises questions regarding the effectiveness of the applied marketing strategies and indicates potential gaps between planning and execution, as well as the presence of internal or external factors yet to be fully addressed. A quantitative approach was employed in this research using survey methods. Data collection involved field observation, interviews, literature review, questionnaire distribution to consumers, and documentation. The data were analyzed using Smart PLS 3.8 software, including convergent validity testing, reliability testing, classical assumption testing, goodness of fit analysis, coefficient of determination, structural equation modeling, and hypothesis testing. The results revealed that service quality, product diversity, and experiential marketing each have a significant and positive effect on consumer trust. Moreover, these three variables also directly and positively influence consumers’ repurchase intention. Additionally, consumer trust was found to significantly mediate the relationship between service quality, product diversity, and experiential marketing and repurchase intention. Thus, consumer trust plays a strategic role in strengthening the marketing variables' impact on customer loyalty. These findings imply the importance of consistently managing customer experience, enhancing service quality, and offering diverse product options to build and maintain trust. Repurchase intention can be increased through strategies focused on both the emotional and functional experiences of consumers during their interaction with the store. This research offers practical insights for retail management in designing marketing strategies centered on long-term consumer relationships.